2019
DOI: 10.3389/fimmu.2019.01496
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Reprogramming of Macrophage Responsiveness to Bacterial Lipopolysaccharide in Obesity

Abstract: The mechanisms by which obesity may alter immune responses to pathogens are poorly understood. The present study assessed whether the intrinsic responsiveness of resident macrophages to bacterial lipopolysaccharide (LPS) is reprogrammed in high-fat diet (HFD)-induced obesity. Macrophages from adipose tissue, lung alveoli, and the peritoneal cavity were extracted from obese rats on a HFD or from their lean counterparts, and subsequently studied in culture under identical conditions. CD45 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…On the day of the LPS challenge, rats of the LFD and HFD groups weighed 479 ± 26 g and 611 ± 41 g, respectively. This difference in body mass was statistically significant (p = 0.009), and is consistent with the increased adiposity reported for rats under the same HFD regimen [31]. At the ambient temperature of 22ºC, the rats responded to 300 μg of LPS with a biphasic drop in T c (Figure 1).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…On the day of the LPS challenge, rats of the LFD and HFD groups weighed 479 ± 26 g and 611 ± 41 g, respectively. This difference in body mass was statistically significant (p = 0.009), and is consistent with the increased adiposity reported for rats under the same HFD regimen [31]. At the ambient temperature of 22ºC, the rats responded to 300 μg of LPS with a biphasic drop in T c (Figure 1).…”
Section: Resultssupporting
confidence: 85%
“…It should be considered, though, that global changes in cytokine ratios do not necessarily reflect what happens at the tissue level. Indeed, a recent study [31] has revealed that obesity reprograms the cytokine responses of macrophages to LPS in a sitespecific manner, with the responses of adipose tissue and peritoneal macrophages shifting in opposite directions. How important this sitespecific reprogramming is to LPS-induced thermoregulatory responses remains a question for future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Separately, multiple studies investigating the relation between TLR4 deficiency and diabetes analyzed either adipose tissue macrophages (54) or peritoneal macrophages (53) to draw their conclusions. Macrophage phenotypes can vary depending on their environmental niche, and thereby drawing correlations about diabetic wound macrophages from other macrophage populations may be inadequate (59). Last, prior studies that have investigated the impact of TLR4 deficiency on diabetes and wound healing (54,58) have mostly been observational, whereas wound healing is observed in a whole-body TLR4-deficient murine model and not an in vivo cell-specific depletion model.…”
Section: Discussionmentioning
confidence: 99%
“…This results in increased neutrophil sequestration and impaired migration into the alveolar space during times of infectious insult, as well as M1 polarization of resident alveolar macrophages. In an LPS model of bacterial sepsis, the obese state promoted switching to the M1 (proinflammatory) phenotype, increasing alveolar TNF-α/IL-10 ratio, and reprogramming of adipose tissue macrophages to a state of increased responsiveness ( 60 , 61 ). NK cells are a subset of lymphocytes that respond swiftly to infected host cells with lytic substances such as perforins and granzymes ( 62 ).…”
Section: Innate Immunity and Obesitymentioning
confidence: 99%